Physicochemical and structural properties of lidocaine-based ionic liquids with anti-inflammatory anions. Issue 24 (6th April 2020) - Panić, Jovana; Tot, Aleksandar; Janković, Nenad; Drid, Patrik; Gadžurić, Slobodan; Vraneš, Milan
Abstract : A detailed theoretical and physico-chemical investigation of synthesized pharmaceutically active ionic liquids. Abstract : The purpose of this paper was to examine the density, viscosity and electrical conductivity at different temperatures, as well as the thermal stability and structural properties of previously reported ionic liquids based on active pharmaceutical ingredients. Lidocaine-based ionic liquids, with ibuprofen and salicylate as counterion, were prepared first. Their structures were confirmed by infrared, mass and 1 H and 13 C nuclear magnetic resonance spectroscopy. The Newtonian behaviour of lidocaine ibuprofenate was confirmed from viscosity measurement results, while it was impossible to determine for lidocaine salicylate. The interactions and structures of the studied ionic liquids were analyzed based on the measured density values, viscosity, electrical conductivity, and calculated values of thermal expansion coefficients and activation energy of viscous flow. From a theoretical aspect, DFT and MD calculations were performed. The obtained descriptors and radial distribution, as well as structural functions, were used to understand the structural organization of the synthesized ionic liquids.